Complex Commingling: Nucleoporins and the Spindle Assembly Checkpoint - Ikram Mossaid; Birthe Fahrenkrog (Cells, 2015)
The segregation of the chromosomes during mitosis is an important process, in which the replicated DNA content is properly allocated into two daughter cells. To ensure their genomic integrity, cells present an essential surveillance mechanism known as the spindle assembly checkpoint (SAC), which monitors the bipolar attachment of the mitotic spindle to chromosomes to prevent errors that would result in chromosome mis-segregation and aneuploidy. Multiple components of the nuclear pore complex (NPC), a gigantic protein complex that forms a channel through the nuclear envelope to allow nucleocytoplasmic exchange of macromolecules, were shown to be critical for faithful cell division and implicated in the regulation of different steps of the mitotic process, including kinetochore and spindle assembly as well as the SAC. In this review, we will describe current knowledge about the interconnection between the NPC and the SAC in an evolutional perspective, which primarily relies on the two mitotic checkpoint regulators, Mad1 and Mad2. We will further discuss the role of NPC constituents, the nucleoporins, in kinetochore and spindle assembly and the formation of the mitotic checkpoint complex during mitosis and interphase.